2020
DOI: 10.1128/iai.00147-20
|View full text |Cite
|
Sign up to set email alerts
|

Niche- and Gender-Dependent Immune Reactions in Relation to the Microbiota Profile in Pediatric Patients with Otitis Media with Effusion

Abstract: Otitis media with effusion (OME) is a common inflammatory disease, primarily affecting children. OME is defined as a chronic low-grade inflammation of the middle ear (ME), without any signs of infection and with effusion persisting in the ME for more than three months. The precise pathogenesis is, however, not fully understood. Here, we comprehensively characterized and compared the host immune responses (inflammatory cells and mediators) and the overall microbial community composition (microbiota) present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
(134 reference statements)
0
14
0
1
Order By: Relevance
“…In contrast, C . propinquum was reported to correlate with anti-flammatory mediators in human nasopharynx [ 61 ]. Whether and what type of immune responses the Corynebacterium species may elicit in vivo to imped Spn colonization thus await future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, C . propinquum was reported to correlate with anti-flammatory mediators in human nasopharynx [ 61 ]. Whether and what type of immune responses the Corynebacterium species may elicit in vivo to imped Spn colonization thus await future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these classic otopathogens, multiple 16S rRNA gene sequencing studies of OME middle ear effusion also reported high levels of Alloiococcus otitis, Corynebacterium otitidis (formerly Turicella otitidis [4]), Pseudomonas spp., and Staphylococcus spp. (Staphylococcus aureus, Staphylococcus auricularis, and Staphylococcus epidermidis) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). It is, however, still uncertain if these taxa, many of which are residents of the ear canal (17,18) or the healthy URT (19), contribute to middle ear disease.…”
mentioning
confidence: 99%
“…The mechanisms by which the middle ear microbiome, in concert with that of the nasopharyngeal microbiome, may impact on the development and pathogenesis of OM remain largely unknown. This is a growing area of investigation (Schenck et al, 2016;Enoksson et al, 2020;Marsh et al, 2020), as the presence of a healthy middle ear microbiome is controversial (Johnston et al, 2019) with one key study in adults finding no evidence of bacterial colonisation of the middle ear using microscopy and culture techniques (Jervis-Bardy et al, 2019). The inflammation that defines OM, however, is induced by invading respiratory viral pathogens and dysregulated commensal bacterial populations within the nasopharynx, which then migrate through the upper respiratory tract via the eustachian tubes to infect the middle ear.…”
Section: Bacterial and Viral Otopathogensmentioning
confidence: 99%
“…The healthy middle ear of both humans and animal models of OM is host to immunocompetent cell types, although not in significantly high numbers until infiltration occurs during AOM (Jecker et al, 1996;Jecker et al, 2001;Suenaga et al, 2001) or COME (Enoksson et al, 2020). Mast cells and macrophages are the predominant cell types in non-inflamed middle ear, with dendritic cells and macrophages present in the tympanic membrane (Ichimiya et al, 1990;Mittal et al, 2014b) These antigen-presenting cell phenotypes provide a mechanism for interconnection of the local innate mucosal immune response with the more specific adaptive immune system (Ichimiya et al, 1997).…”
Section: Immunocompetent Cell Types Within the Mucosal Epitheliummentioning
confidence: 99%
See 1 more Smart Citation